9x-4(x-3)=72

Simple and best practice solution for 9x-4(x-3)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4(x-3)=72 equation:


Simplifying
9x + -4(x + -3) = 72

Reorder the terms:
9x + -4(-3 + x) = 72
9x + (-3 * -4 + x * -4) = 72
9x + (12 + -4x) = 72

Reorder the terms:
12 + 9x + -4x = 72

Combine like terms: 9x + -4x = 5x
12 + 5x = 72

Solving
12 + 5x = 72

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 5x = 72 + -12

Combine like terms: 12 + -12 = 0
0 + 5x = 72 + -12
5x = 72 + -12

Combine like terms: 72 + -12 = 60
5x = 60

Divide each side by '5'.
x = 12

Simplifying
x = 12

 

See similar equations:

| 498x-403=29x-816 | | 498x-403=29x-500 | | 498x-403=290x-816 | | 490x-406=308x-820 | | 140x-7=240x-8 | | w+41=0 | | 179(x+9)=-289 | | 2000x-4=8-3000x | | 1000x-2000=2000-1000x | | 3x-10=65 | | 24-27(9+6n)=267 | | -14=2(6-k)+6(7+6k) | | 3x+44+(x+20)=180 | | 3=3+4x | | x+14=2x+1 | | 4x-11=13-2x | | 5(9+4n)-7n=3(6n-6)-2n | | 3(1-4x)-1(2X-1)2(2)=7 | | -1=-3r+-2r | | 6=-3(x+2) | | 255=32(38x+23)-21(x-34) | | 9(4h-6)=2(-13-2h) | | 6.8t-10-3.2t=3t-1 | | 3x*11=30x+12 | | 0.2(15z-5)=4(4z+1) | | -4(-3b-2)=56 | | -4x-3(-4+4x)=60 | | -10(17+31x)-9(x+16)=324 | | 10x-14=12-8 | | 7.1p-2.6p+12=6 | | 11=-m | | 4x-12=32 | | -2x+7-10+3x=-1 | | -6=b | | -5x-4(1+2x)=100 | | -15x+10-3x=-6x+8-4x | | 67(r)=43 | | 10v-3v+4-2v=-21 | | 5d-1=-11 | | -3(2k-6)=12 | | 3k-7=14 | | 4(w-3)=8w | | 18=-5y-7 | | 2.7y=-18 | | 9+4y=3(4-y) | | 4d-35=-3 | | 4.7=-8.3q | | 8-2y=2y-2-y | | x-(-74)=-22 | | 11x-24=-2 | | -56=20-(-e) | | 5x+7=2x+4 | | 15a-54=-9 | | 7+4x=10x-11 | | 11xcv+456-35yU=o | | -12x-3=-51 | | 11x-13-27-13x=0 | | 3G-49=-7 | | 5*(x+3)=3*(2x-1) | | -4x-20+9x=-5 | | -12x+3=51 | | 2a+5b=10a+14b | | 5X+12=8X-12 | | -2x-4=8 | | 2(x+4)+36=-3x |